Two magnesium transporters in the chloroplast inner envelope essential for thylakoid biogenesis in Arabidopsis. Issue 2 (22nd July 2022) - Zhang, Bin; Zhang, Chi; Tang, Renjie; Zheng, Xiaojiang; Zhao, Fugeng; Fu, Aigen; Lan, Wenzhi; Luan, Sheng
Summary: Magnesium (Mg 2+ ) serves as a cofactor for a number of photosynthetic enzymes in the chloroplast, and is the central atom of the Chl molecule. However, little is known about the molecular mechanism of Mg 2+ transport across the chloroplast envelope. Here, we report the functional characterization of two transport proteins in Arabidopsis: Magnesium Release 8 (MGR8) and MGR9, of the ACDP/CNNM family, which is evolutionarily conserved across all lineages of living organisms. Both MGR8 and MGR9 genes were expressed ubiquitously, and their encoded proteins were localized in the inner envelope of chloroplasts. Mutations of MGR8 and MGR9 together, but neither of them alone, resulted in albino ovules and chlorotic seedlings. Further analysis revealed severe defects in thylakoid biogenesis and assembly of photosynthetic complexes in the double mutant. Both MGR8 and MGR9 functionally complemented the growth of the Salmonella typhimurium mutant strain MM281, which lacks Mg 2+ uptake capacity. The embryonic and early seedling defects of the mgr8/mgr9 double mutant were rescued by the expression of MGR9 under the embryo‐specific ABI3 promoter. The partially rescued mutant plants were hypersensitive to Mg 2+ deficient conditions and contained less Mg 2+ in their chloroplasts than wild‐type plants. Taken together, we conclude that MGR8 and MGR9 serve as Mg 2+ transporters and are responsible for chloroplast Mg 2+ uptake.